Transformational Leadership, Organizational Culture, and Employee Engagement: A Systematic Literature Review - Priyanti, Indri Ayu Dani; Nisa’, Zuhrotun; Yuniawan, Ahyar (LifeSciFi, 2025)
This research investigates the connections among transformational leadership, organizational culture, and the results achieved by the organizational outcomes—such as changes, innovativeness, employee retention, and performance—across various institutional contexts. The researchers used a qualitative approach, employing structural equation modelling, regression analysis, and mediation frameworks that involved employee engagement and job satisfaction. The findings consistently show that transformational leadership positively significant influences organizational outcomes, both directly and indirectly through mediating variables such as organizational culture and employee engagement. Organizational culture shapes employee behavior, improves performance, and increases responsiveness to change. Meanwhile, employee engagement acts as a bridge linking leadership to both employee retention and organizational performance. In different settings, such as education and business, transformational leadership nurtures a positive culture that enhances innovation and promotes employee commitment. These results underscore the importance of developing leadership programs that support transformational practices and of establishing cultural frameworks aligned with strategic goals. This study contributes to the current understanding of leadership and human resource development by offering empirical evidence from a multinational and cross-sector perspective, thus delivering practical insights for driving organizational change and attaining excellence.